CITIES AS SMART TERRITORIAL HUBS. EVOLUTION, BENCHMARK AND THE FUTURE: THE MASDAR CASE STUDY - Oliveira, Fernanda Paula (2022)
In the last 15 years, the concept of smart cities has been gaining more and more relevance and, as well, dissipating throughout the world. Cities assume a fundamental role for the new realities that the planet faces, both in terms of sustainability and communication and information technologies (ICT), many other social challenges, with an impact on the most diverse sectors of activity. In this article, we intend not only to demonstrate the importance of this concept and the implementation of smart cities, but also of a concept that arises with this – eco- city – very present in the city under study, the city of Masdar, located in the United Arab Emirates. As main conclusions, it is important to highlight that there is still a long way for the implementation of more examples such as the city of Masdar and that this evolution will certainly take place at different paces and with different intensities considering the disparity between the different regions, the different countries and different continents, that will be synonymous of a proliferation of examples with different successes and scopes, which must be monitored and duly followed up in the future.